Advancing SDG 4 through Deep Learning Approaches: Reconstructing Student Learning from Metacognitive and Higher-Order Thinking Skills Perspectives - Sri Usodoningtyas; Ekohariadi Ekohariadi; Maspiyah Maspiyah; Ratna Suhartini; Luthfiyah Nurlaela (Journal of Current Studies in SDGs, 2026)
Objective: To reconstruct student learning within the context of sustainable quality education by exploring the integration of deep learning approaches, metacognition, and Higher-Order Thinking Skills (HOTS) in higher education. The study responds to the persistent dominance of memorization-oriented and procedural learning practices that limit students’ cognitive development and lifelong learning capacities. Methods: A qualitative conceptual design was employed using thematic analysis of scholarly literature published between 2022 and 2026. Relevant studies on deep learning, metacognition, HOTS, and sustainable higher education were systematically reviewed to identify key themes and conceptual relationships. Results: The analysis demonstrates that deep learning promotes meaningful cognitive engagement, reflective awareness, and active knowledge construction. Metacognitive regulation functions as a central mechanism linking deep learning and HOTS through planning, monitoring, and evaluating learning processes. Furthermore, inquiry-based learning, reflective activities, and authentic problem-solving experiences enhance students’ analytical reasoning, creativity, adaptability, and critical thinking, which are essential competencies for sustainable learning and future workforce readiness. Novelty: The proposes an integrated conceptual framework that connects deep learning, metacognition, and HOTS within the broader agenda of Sustainable Development Goal 4 (Quality Education). The framework offers a comprehensive perspective for transforming student learning from surface-level knowledge acquisition to meaningful and reflective learning, while providing theoretical insights for educators and researchers seeking to promote sustainable and transformative educational practices in higher education.